Antimicrobial activity of ethanolic Leaf Extracts of Ocimum basilicum on some bacteria - M.Jassim, Zainab. (Al-Qadisiyah Journal of Pure Science, 2018)
This study was designed to determine the in-vitro antimicrobial effects of ethanolic leaf extract of Ocimum basilicum, by Agar well diffusion antimicrobial bioassay. Results showed a broad spectrum of activity since the extracts inhibit the growth of both gram positive (Staphylococcus aureus, Streptococcus pneumonia and Enterococcus faecalis) and gram negative (Escherichia coli and Pseudomonas aeruginosa) . Antimicrobial assay of 400%, 200% and 100% mg/ml ethanolic extracts shows very potent antimicrobial agent on both gram positive S.auerus (highest inhibition zone 13 mm) and gram negative bacterial isolates.